Pengaruh Jumlah DPK dan CAR Terhadap Alokasi Pembiayaan Usaha Mikro Kecil dan Menengah pada Bank BCA Syariah Tahun 2017-2019 - Safitri, Aulia; jumarni, jumarni (Islamic Banking and Finance, 2022)
This study discusses the effect of DPK and CAR on the allocation of financing for micro, small and medium enterprises at Bank BCA Syariah in 2017-2019. This study aims to examine the effect of third-party funds and CARon the allocation of financing for micro, small and medium enterprises and how much they affect. The analysis of this study uses independent variables, namely thirdparty funds, the independent variable is the financing of micro, small and medium enterprises as measured by the financial performance of MSMEs based on the CAR indicator, which is comparing Capital with ATMR. Based on the purpose of the study, this research is a type of quantitative research using a panel data regression approach. This technique is used to assist in processing relevant data obtained from financial statements